Current practices in pediatric continuous kidney replacement therapy: a systematic review-guided multinational modified Delphi consensus study - Fuhrman, Dana Y.; Gist, Katja M.; Akcan-Arikan, Ayse (Pediatric nephrology (Berlin, West), 2023)
Background Continuous kidney replacement therapy (CKRT) has become an integral part of the care of critically ill children. However, uncertainty exists regarding the current state of how CKRT is prescribed and delivered in children. The main objective of this study was to identify the current practices for pediatric CKRT. Methods We conducted a systematic review of the literature from 2012 to 2022 to identify data regarding CKRT timing of initiation, dosing, anticoagulation, fluid removal, and quality monitoring. Using this data, we then performed a two-round modified Delphi process using a multinational internet-assisted survey of prescribers of CKRT. Results The survey was constructed using 172 articles that met inclusion criteria (12% of studies were pediatric focused). A total of 147 and 126 practitioners completed the survey in rounds 1 and 2, respectively. Participants represented Europe (9.5–11.6%) and North America including pediatric intensivists, nephrologists, and advance practice providers. Consensus (defined as a ≥ 75% participant response of “sometimes” or “always”) was achieved for 26 statements. There was consensus in the practices of CKRT initiation, dosing, method of anticoagulation, and fluid removal. In contrast, there appears to be greater variability in the methods used for monitoring anticoagulation and the quality of the delivered treatment. Conclusions Our study results suggest that the current state of pediatric CKRT practice is reflective of the literature over the last 10 years, which is largely based on the care of adult patients. This data provides a framework to study best practices to further improve outcomes for children receiving CKRT. Graphical abstract A higher resolution version of the Graphical abstract is available as Supplementary information